Recognizing Connections Between Intimate Partner Sexual Violence and Pornography. (November 2021) - Tarzia, Laura; Tyler, Meagan
In this article, we call for a more concerted effort to understand the ways in which pornography might be used in, and contribute to, intimate partner sexual violence (IPSV). We seek to address this through an overview of existing work and the introduction of data from an Australian-based project on women's experiences of IPSV, where pornography use was an unexpected finding. Furthermore, we argue that there is a pressing need to address such issues now, given the increasing mainstreaming of pornography. Our findings contribute toward a better understanding of the context and dynamics of IPSV for women and suggest that pornography ought to be a greater focus in prevention efforts.